1975
DOI: 10.1002/jsfa.2740260807
|View full text |Cite
|
Sign up to set email alerts
|

The cuticles of Citrus species. Composition of leaf and fruit waxes

Abstract: Seasonal changes in the surface waxes of the leaves and fruits of four species of Citrus have been examined. Leaf wax deposits ranging from 20pg/cm2 in orange to 31 pg/cm2 in lemon were consistent during all except the most juvenile stages of growth whereas the surface waxes of the fruits showed considerable variation, the most pronounced being a 58% decrease in the wax deposits of lemon between July and October. Hydrocarbons (23-66 %), primary alcohols (6-38%) and fatty acids were important constituents of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
52
2
8

Year Published

1981
1981
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 24 publications
12
52
2
8
Order By: Relevance
“…The epicuticular wax yield of Fortune mandarin fruits from the three orchards studied was similar to that found for mandarin fruits in Rhodes (Greece), 13 Dancy mandarins in Florida (USA) 14 and Satsuma mandarins in Valencia (Spain), but was lower than for Navelina oranges growing in the same citrus area. 7 The secretion of epicuticular wax was continuous and its quantity increased during fruit ripening, despite the increase in fruit surface area (Fig 1).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The epicuticular wax yield of Fortune mandarin fruits from the three orchards studied was similar to that found for mandarin fruits in Rhodes (Greece), 13 Dancy mandarins in Florida (USA) 14 and Satsuma mandarins in Valencia (Spain), but was lower than for Navelina oranges growing in the same citrus area. 7 The secretion of epicuticular wax was continuous and its quantity increased during fruit ripening, despite the increase in fruit surface area (Fig 1).…”
Section: Discussionsupporting
confidence: 66%
“…14 In mandarins in Rhodes (Greece) the order was alkanes b aldehydes b fatty acids b primary alcohols, whereas in clementines in the same location the main constituents were aldehydes, alkanes, primary alcohols and fatty acids. 13 Normally, alkanes constituted the main component in oranges and mandarins. However, the main component of grapefruit epicuticular wax was triterpenoids, followed by aldehydes, hydrocarbons and alcohols.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of age on the development of epicuticular wax layers were less predictable. Tulloch (1973), Baker, Procopiou andHunt (1975) and Freeman, Albrigo and Biggs (1979a, b) have shown that the thickness and composition of epicuticular wax deposits vary with leaf age but these workers did not distinguish between the changes occurring separately at the adaxial and abaxial surfaces. In general, their studies showed that the amount of wax per unit area fluctuated during growth leading to an overall decline on most leaves.…”
Section: Discussionmentioning
confidence: 99%
“…This hydrophobic wax layer confers essential ecophysiological functions, including the regulation of water loss (Albrigo 1972), protection against pathogen penetration (Schirra and D'hallewin 1997;Schirra et al 2000;Dore et al 2009), and exchanges of gases through the cuticle (Ben-Yehoshua et al 1985;El-Otmani et al 1986). Several studies have reported that the amount, composition and structure of citrus cuticular waxes vary widely among cultivars, organs and developmental states (Baker et al 1975;Freeman et al 1979;El-Otmani and Coggins 1985;Sala et al 1992;Cajuste et al 2010). Recently, epicuticular waxes have been selectively separated from the mature fruit surfaces of Satsuma mandarin (Citrus unshiu) and 'Newhall' navel orange (Citrus sinensis) by gum arabic and investigated by gas chromatography and mass spectrometry (GC-MS).…”
Section: Introductionmentioning
confidence: 98%